Manajemen Penanaman Karakter Melalui Strategi Pencegahan Bullying di SD Negeri 1 Garung Kabupaten Wonosobo - Saputro, Hendi Wicaksono (Universitas Sarjanawiyata Tamansiswa, 2024)
This research was conducted at SD Negeri 1 Garung to 1) determine the management of character development in the framework of bullying prevention strategies, 2) to analyze the factors that cause bullying, 3) to analyze the impact of bullying on students, and 4) to determine bullying prevention strategies. This research is qualitative research with data sources from school principals, teachers, school committees, parents and students at SD Negeri 1 Garung using a purposive sampling technique. Data collection techniques were carried out using in-depth interviews, role observation and document analysis. Then the data analysis technique uses the Miles and Hubberman method which begins with data collection, data reduction, data presentation, and conclusions. Meanwhile, checking the validity of the data was carried out by source triangulation. The result of this research is that character cultivation management is carried out through a process of planning, organizing, actuating and Controlling. Character cultivation activities are carried out using familiarization and are integrated in the implementation of teaching and learning activities in all subjects and extracurricular activities. This integrated character-building activity is a strategy for preventing bullying at SD Negeri 1 Garung.